2007
DOI: 10.1007/s10340-006-0159-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal parasitism of cereal aphids in a Mediterranean arable crop system

Abstract: We monitored winter cereal Welds in a Mediterranean arable crop system to obtain information about the aphid parasitoid species composition and the aphid-parasitoid interactions through the whole cropping cycle. Nine species of aphid primary parasitoids (Hymenoptera, Braconidae, Aphidiinae) were identiWed. The most abundant species were Aphidius rhopalosiphi, Aphidius matricariae, Aphidius ervi and Lysiphlebus testaceipes. The genus Aphelinus sp. (Hym., Aphelinidae) was also identiWed. We determined seasonal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
36
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 15 publications
4
36
1
4
Order By: Relevance
“…Several authors reported on the oligophagous nature of A. ervi in laboratory and field studies (Sigsgaard 2000;Lumbierres et al 2007;Starv et al 2007). Of the aphid species parasitized by A. ervi, at least 15 are known to occur in South Africa according to Millar (1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors reported on the oligophagous nature of A. ervi in laboratory and field studies (Sigsgaard 2000;Lumbierres et al 2007;Starv et al 2007). Of the aphid species parasitized by A. ervi, at least 15 are known to occur in South Africa according to Millar (1990).…”
mentioning
confidence: 99%
“…Of the aphid species parasitized by A. ervi, at least 15 are known to occur in South Africa according to Millar (1990). These include the Macrosiphini Acyrthosiphon kondoi Shinji, A. pisum, A. malvae (Mosley), Aulacorthum solani (Kaltenbach), Diuraphis noxia (Kurdjumov), M. euphorbiae, M. rosae (L.), Metopolophium dirhodum (Walker), Myzus persicae (Sulzer), Sitobion avenae (F.) and S. fragariae (Walker) (Starv 1976;Marsh 1977;Takada 2002;Tomanovi et al 2003;Lumbierres et al 2007;Starv et al 2007;Boivin et al 2012), and the four Aphidini Aphis gossypii Glover, Rhopalosiphum maidis (Fitch), R. padi (L.), and Schizaphis graminum (Rondani) (Marsh 1977;Tomanovi et al 2003;Lumbierres et al 2007;Starv et al 2007).…”
mentioning
confidence: 99%
“…Kompletan spisak vrsta parazitoida koji su vezane za žitne vaši na prostoru Evrope obuhvata oko 20 vrsta (Powell, 1982;Tomanović & Brajković, 2001;Sigsgaard, 2002;Starý, 2006;Lumbierres et al, 2007;Starý & Havelka, 2008;Tomanović et al, 2008Tomanović et al, , Žikić et al, 2012. Indentifikacija pojedinih taksona može biti teška ili problematična, pa se u nekim radovima rezultati daju samo na nivou roda, naročito u slučaju roda Aphelinus, a u manjoj meri Praon i Aphidius (Sigsgaard, 2002;Starý, 2006;Lumbierres et al, 2007).…”
Section: Kompleks Biljnih Vašiju I Njihovih Parazitoida Na Pšeniciunclassified
“…Indentifikacija pojedinih taksona može biti teška ili problematična, pa se u nekim radovima rezultati daju samo na nivou roda, naročito u slučaju roda Aphelinus, a u manjoj meri Praon i Aphidius (Sigsgaard, 2002;Starý, 2006;Lumbierres et al, 2007). U tabeli 4 je dat uporedni prikaz izabranih radova i vrsta koje se u njima navode.…”
Section: Kompleks Biljnih Vašiju I Njihovih Parazitoida Na Pšeniciunclassified
See 1 more Smart Citation